Types, Functions, and Morphological Process of Reduplication in Sumbawa Besar Dialect - Ismiati Ismiati (Universitas Pendidikan Mandalika, 2021)
The study discusses the types, functions, and morphological processes of Reduplication in the Sumbawa Besar dialect. Data was taken from recorded conversation, which naturally occurred among the native speakers of Sumbawa Besar Dialect. The native were also interviewed to gain deeply information. Finding of this study describes some types of Reduplication in Sumbawa Besar Dialect namely full Reduplication, partial Reduplication, and reduplication variation of phoneme. In full Reduplication, the word is fully repeated without any additional morpheme or phoneme to the base word. For example, the base word ‘lao’ (slow) is fully reduplicated becomes ‘lao-lao’ (slowly). Partial Reduplication is partly the repetition of the base word. For example, ‘Barema’ (together) is the base form that is reduplicated by repeating the last phoneme to become ‘Barema-rema’. ‘Barema’ is the base and ‘rema’ is its phoneme which is repeated to form Reduplication. Reduplication variation of phoneme is the type of Reduplication which combines two different word classes and meaning to create meaningful Reduplication. As example, ‘sedo-gaso’ (supplies). ‘sedo’ is the first base word and the second word is ‘gaso’. Those are combined to create Reduplication becomes ‘sedo-gaso’ (supplies). Function of Reduplication in Sumbawa Besar Dialect was to change word classes as verb is changed into noun and change singular form to plural form of the noun. In example, ‘Mangan’ (eat) is the word class of verb which is changed into the word class of noun ‘Mangan’-‘Mangan’ (a picnic) in its Reduplication. In another example, the word Anak (a child) is the singular form of noun is changed into plural form Anak-dadi (children) in its Reduplication.